An AMP-activated protein kinase-stabilizing peptide ameliorates adipose tissue wasting in cancer cachexia in mice - Rohm, Maria; Schäfer, Michaela; Laurent, Victor; Üstünel, Bilgen Ekim; Niopek, Katharina; Algire, Carolyn; Hautzinger, Oksana; Sijmonsma, Tjeerd P; Zota, Annika; Medrikova, Dasa; Pellegata, Natalia S; Ryden, Mikael; et al. (Nature medicine, 2016)
Cachexia represents a fatal energy-wasting syndrome in a large number of patients with cancer that mostly results in a pathological loss of skeletal muscle and adipose tissue. Here we show that tumor cell exposure and tumor growth in mice triggered a futile energy-wasting cycle in cultured white adipocytes and white adipose tissue (WAT), respectively. Although uncoupling protein 1 (Ucp1)-dependent thermogenesis was dispensable for tumor-induced body wasting, WAT from cachectic mice and tumor-cell-supernatant-treated adipocytes were consistently characterized by the simultaneous induction of both lipolytic and lipogenic pathways. Paradoxically, this was accompanied by an inactivated AMP-activated protein kinase (Ampk), which is normally activated in peripheral tissues during states of low cellular energy. Ampk inactivation correlated with its degradation and with upregulation of the Ampk-interacting protein Cidea. Therefore, we developed an Ampk-stabilizing peptide, ACIP, which was able to ameliorate WAT wasting in vitro and in vivo by shielding the Cidea-targeted interaction surface on Ampk. Thus, our data establish the Ucp1-independent remodeling of adipocyte lipid homeostasis as a key event in tumor-induced WAT wasting, and we propose the ACIP-dependent preservation of Ampk integrity in the WAT as a concept in future therapies for cachexia.
Keywords: AMP-Activated Protein Kinases; proteiny regulující apoptózu; Neoplasms; termogeneze; Uncoupling Protein 1; techniky in vitro; Apoptosis Regulatory Proteins; metabolismus lipidů; bílá tuková tkáň; Adipose Tissue, White; Cachexia; peptidové fragmenty; kultivované buňky; lipolýza; Animals; bílé tukové buňky; uncoupling protein 1; Adipocytes, White; zvířata; Lipolysis; Lipid Metabolism; kachexie; Thermogenesis; myši; Cells, Cultured; nádory; Mice; lipogeneze; Peptide Fragments; proteinkinasy aktivované AMP; Lipogenesis; In Vitro Techniques